The National Immunization Technical Advisory Group in Israel - Chen Stein-Zamir; Shmuel Rishpon (BMC, 2021)
Abstract National Immunization Technical Advisory Groups (NITAGs) are defined by the World Health Organization as multidisciplinary groups of health experts who are involved in the development of a national immunization policy. The NITAG has the responsibility to provide independent, evidence-informed advice to the policy makers and national programme managers, on policy issues and questions related to immunization and vaccines. This paper aims to describe the NITAG in Israel. The Israeli NITAG was established by the Ministry of Health in1974. The NITAG's full formal name is "the Advisory Committee on Infectious Diseases and Immunizations in Israel". The NITAG is charged with prioritizing choices while granting maximal significance to the national public health considerations. Since 2007, the full minutes of the NITAG's meetings have been publicly available on the committee's website (at the Ministry of Health website, in Hebrew). According to the National Health Insurance Law, all residents of Israel are entitled to receive universal health coverage. The health services basket includes routine childhood immunizations, as well as several adult and post - exposure vaccinations. The main challenge currently facing the NITAG is establishing a process for introducing new vaccines and updating the vaccination schedule through the annual update of the national health basket. In the context of the annual update, vaccines have to "compete" with multiple medications and technologies which are presented to the basket committee for inclusion in the national health basket. Over the years, the Israeli NITAG's recommendations have proved essential for vaccine introduction and scheduling and for communicable diseases control on a national level. The NITAG has established structured and transparent working processes and a decision framework according to WHO standards, which is evidence-based and country-specific to Israel. The recent global COVID-19 pandemic is a major concern for all countries as well as a challenge for NITAGs. Currently, the NITAGs have a key role in advising both on sustainment of the routine immunization programs and on planning of the COVID-19 vaccination campaigns, with ongoing updates and collaboration with the Ministry of Health and health organizations.